Prerequisite – Solving Recurrences, Different types of recurrence relations and their solutions, Practice Set for Recurrence Relations

The sequence which is defined by indicating a relation connecting its general term a_{n} with a_{n-1}, a_{n-2}, etc is called a **recurrence relation** for the sequence.

### Types of recurrence relations

**First order Recurrence relation :-**A recurrence relation of the form :**a**for n>=1_{n}= ca_{n-1}+ f(n)

where c is a constant and f(n) is a known function is called linear recurrence relation of first order with constant coefficient. If f(n) = 0, the relation is homogeneous otherwise non-homogeneous.**Example :-**x_{n}= 2x_{n-1}– 1, a_{n}= na_{n-1}+ 1, etc.**Question :-**Solve the recurrence relation T(2^{k}) = 3T(2^{k-1}) + 1, T(1) = 1.

Let T(2^{k}) = a_{k}. Therefore, a_{k}= 3a_{k-1}+ 1

Multiplying by x^{k}and then taking sum,

Σa_{k}x^{k}= 3Σa_{k-1}x^{k}+ Σx^{k}——> (1)

Σa_{k-1}x^{k}= [a_{0}x + a_{1}x^{2}+ ……]

= x[a_{0}+ a_{1}x + ……] = x[G(x)]

(1) becomes

G(x) – 3xG(x) – x/(1-x) = 0

G(x)(1-3x) – x/(1-x) = 0

G(x) = x/[(1-x)(1-3x)] = A/(1-x) + B/(1-3x)

–> A = -1/2 and B = 3/2

G(x) = (3/2)Σ(3x)^{k}– (1/2)Σ(x)^{k}

Coefficient of x^{k}is, a_{k}= (3/2)3^{k}– (1/2)1^{k}

So, a_{k}= [3^{k+1}– 1]/2.**Second order linear homogeneous Recurrence relation :-**A recurrence relation of the form

**c**——> (1)_{n}a_{n}+ c_{n-1}a_{n-1}+ c_{n-2}a_{n-2}= 0

for n>=2 where c_{n}, c_{n-1}and c_{n-2}are real constants with c_{n}!= 0 is called a second order linear homogeneous recurrence relation with constant coefficients.

Solution to this is in form a_{n}= ck^{n}where c, k!=0

Putting this in (1)

c_{n}ck^{n}+ c_{n-1}ck^{n-1}+ c_{n-2}ck^{n-2}= 0

c_{n}k^{2}+ c_{n-1}k + c_{n-2}= 0 —–> (2)

Thus, a_{n}= ck^{n}is solution of (1) if k satisfies quadratic equation (2). This equation is called characteristic equation for relation (1).

Now three cases arises,

**Case 1 :**If the two roots k_{1}, k_{2}of equation are real and distinct then, we take

**a**as general solution of (1) where A and B are arbitrary real constants._{n}= A(k_{1})^{n}+ B(k_{2})^{n}**Case 2 :**If the two roots k_{1}, k_{2}of equation are real and equal, with k as common value then, we take

**a**as general solution of (1) where A and B are arbitrary real constants._{n}= (A + Bn)k^{n}**Case 3 :**If the two roots k_{1}and k_{2}of equation are complex then, k_{1}and k_{2}are complex conjugate of each other i.e k_{1}= p + iq and k_{2}= p – iq and we take

**a**as general solution of (1) where A and B are arbitrary complex constants, r = |k_{n}= r^{n}(Acosnθ + Bsinnθ)_{1}| = |k_{2}| = √p^{2}+ q^{2}and θ = tan^{-1}(q/p).

**Question :- **Solve the recurrence relation a_{n} + a_{n-1} – 6a_{n-2} = 0 for n>=2 given that a_{0} = -1 and a_{1} = 8.

Here coefficients of a_{n}, a_{n-1} and a_{n-2} are c_{n} = 1, c_{n-1} = 1 and c_{n-2} = -6 respectively. Hence, characteristic equation is

k^{2} + k – 6 or (k + 3)(k – 2) = 0 ——> (1)

The roots of (1) are k_{1} = -3 and k_{2} = 2 which are real and distinct. Therefore, general solution is

a_{n} = A(-3)^{n} + B(2)^{n}

where A and B are arbitrary constants. From above we get, a_{0} = A + B and a_{1} = -3A + 2B

A + B = -1

-3A + 2B = 8

Solving these we get A = -2 and B = 1

Therefore, a_{n} = -2(-3)^{n} + (2)^{n}

If you like GeeksforGeeks and would like to contribute, you can also write an article using contribute.geeksforgeeks.org or mail your article to contribute@geeksforgeeks.org. See your article appearing on the GeeksforGeeks main page and help other Geeks.

Please write comments if you find anything incorrect, or you want to share more information about the topic discussed above.